Multiplicities of Representations in Algebraic Families - Cai, Li; Fan, Yangyu (Comptes Rendus. Mathématique)
In this short notes, we consider multiplicities of representations in general algebraic families, especially the upper semi-continuity of homological multiplicities and the locally constancy of Euler–Poincaré numbers. This generalizes the main result of Aizenbud–Sayag for unramified twisting families.